Webcams and virtual teams: an impact model. Issue 3 (3rd June 2014) - D. Olson, Joel; D. Appunn, Frank; A. McAllister, Chad; K. Walters, Kimberly; Grinnell, Lynn
Abstract : Purpose: – The paper aims to address the question, "What is the impact of web-based video via webcams on virtual team trust and effectiveness?" Change and evolution in team perceptions over time are described. The result is the creation of a theoretical model describing the effect of webcams on virtual team development. Design/methodology/approach: – A qualitative phenomenological heuristic case study was used to explore the individual expectations and experiences of the team members over a six-week period. To strengthen reliability and validity, two qualitative methods, content analysis and constant comparative analysis — a means of grounded theory, were used to both test the historic basis of the existing literature on trust and effectiveness in virtual teams and to explore how the use of webcams influenced the work, interactions and effectiveness of a virtual team. Both qualitative methods involved different pairs of researchers using inter-rater coefficients to address coding reliability and validity. Results from the two methods were then compared and contrasted. Findings: – The resulting model highlights the importance of ongoing, formal differentiated training on new technology. This research also suggests careful management of technology change and its deployment to enhance outcomes of various organization forms. Research limitations/implications: – Given the nature of the qualitative study, the findings are not generalizable, but may illumine the understanding of webcams and technology adaptation in similar virtual teams. Practical implications: – The resulting model highlights the importance of ongoing, formal differentiated training on new technology. This research also suggests careful management of technology change and its deployment to enhance outcomes of various organization forms. The study incorporates Technology Acceptance Theory and applications of the Kirton Adaptation-Innovation Inventory. Originality/value: – With the increase in bandwidth on the Internet, technologies such as webcams have become more viable for use in virtual teams.